Rethinking the attractiveness of EU labour immigration policies : comparative perspectives on the EU, the US, Canada and beyond - Carrera, Sergio (Political scientist); Guild, Elspeth; Eisele, Katharina, 1983- (Centre for European Policy Studies, 2014)
Is Europe's immigration policy attractive? One of the priorities driving current EU debates on labour immigration policies is the perceived need to boost Europe's attractiveness vis-á-vis 'talented' and 'highly skilled' immigrants. The EU sees itself playing a role in persuading immigrants to choose Europe over other competing destinations, such as the United States or Canada. This book critically examines the determinants and challenges characterizing discussions focused on the attractiveness of labour migration policies in the EU as well as other international settings. It calls for re-thinking some of the most commonly held premises and assumptions underlying the narratives of 'attractiveness' and 'global competition for talent' in migration policy debates. How can an immigration policy, in fact, be made to be 'attractive' and what are the incentives at play (if any)? A multidisciplinary team of leading scholars and experts in migration studies address the main issues and challenges related to the role played by rights and discrimination, qualifications and skills, and matching demand and supply in needs-based migration policies. The experiences in other jurisdictions such as South America, Canada and the United States are also covered. Are these countries indeed so 'attractive' and 'competitive,' and if so what makes them more attractive than the EU? On the basis of the discussions and findings presented across the various contributions, the book identifies a number of priorities for policy formulation and design in the next generation of EU labour migration policies. In particular, it highlights important initiatives that the new European Commission should focus on in the years to come.